Transgenders in India: An Introduction - Mishra, Veerendra (London Routledge, 2024)
This introductory volume studies the challenges faced by the transgender community in India. It traces the history of the representation of the community in Hindu texts to understand the evolution of their status within Indian society. The book looks at various themes such as the concept of establishing identity through the processes of 'coming out' and 'transitioning' and analyses how race, ethnicity, sexual orientation, class, nation, religion, and ability have cross-influenced to shape the transgender experience and trans culture across and beyond the binary. Lucid and topical, the book debunks myths and critiques the stigma and discrimination surrounding the transgender community. It will be an essential read for scholars and researchers of gender studies, queer studies, exclusion and discrimination studies, political science, sociology, social anthropology, and South Asian studies
Keywords: Transgender people-India; Transphobia-India; Gender